PROCESSED TILAPIA FISH IN SIANTAR SELATAN DISTRICT, SIMALUNGUN REGENCY - Riada Mareny; Jumadiah Wardati; Eka Sihombing (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
South Siantar District, Simalungun Regency is an area around which there are many home industries, for example, craftsmen processing mussels and mussel paste, slaps, ovens, tins, snacks, prawn crackers, fish crackers, mussel crackers and others. Sumorame is one of the Ajibata Villages in the Toba District consisting of several neighborhoods, where each neighborhood has community empowerment activities which are mostly managed by PKK women. Such activities include gatherings for arisan activities, savings and loan cooperatives, training on environmental hygiene and greening, waste banks and other incidental activities. Counseling on Handling of Fishery Products with the theme "Development of Processed Fish in the Context of Increasing Women's Resources and Community Welfare in Siantar Selatan District, Simalungun Regency" is very appropriate considering that fish consumption by the community has reached 43 kilograms per capita per year, this figure will continue to be boosted until it reaches 46 kilograms per capita per year in 2018 and 50 kilograms per capita per year in 2019. This was confirmed by the Minister of Maritime Affairs and Fisheries Susi Pudjiastuti. This counseling uses fish raw materials with the main objective to motivate people to like eating fish. The achievement in this counseling was that all participants, especially PKK women, were able to make their own processed food made from quality and hygienic fish.